Strategi Humas BPSDM Provinsi Jawa Barat Dalam Pengelolaan Konten Media Sosial Instagram @bpsdmjabar - Batubara, Alfindy Selma Serafina; Dewi, Retasari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to determine the public relations strategy of the West Java Province Human Resources Development Agency (BPSDM) in managing social media content, especially on the Instagram platform @bpsdmjabar. With the rapid development of information technology, the role of public relations is not only to convey information, but also to build a positive image of the institution through effective and interactive content delivery. This research method uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation studies. The results showed that the public relations of BPSDM West Java Province implemented the SPARKLE (Smart Providing Answers, Radiating Knowledge with Love Enthusiasm) strategy for content management of general information, activities and entertainment. Evaluation of content performance is done through analysis and audience response using FAIR (Follower, Activity, Interaction, Responsive). This study concludes that content distribution through various Instagram features such as feeds, reels, stories, Highlights helps increase interaction and expand audience reach. In the future, BPSDM can conduct a more in-depth content evaluation by utilizing various analytical tools or using engagement rate calculations to measure the effectiveness of audience interaction and engagement.